Overcoming disease-specific matrix effect in a clinical pharmacokinetic assay using a microfluidic immunoassay technology. (August 2017) - Williams, Kathi; Erickson, Rich; Fischer, Saloumeh Kadkhodayan
Aim: Etrolizumab, a humanized monoclonal antibody, has demonstrated clinical remission in a Phase II study of ulcerative colitis patients. In the Phase III program, a second indication, Crohn's disease was added. The pharmacokinetic ELISA used in the Phase I/II studies in normal human and ulcerative colitis sera exhibited matrix interference in the Crohn's disease population, necessitating implementation of a new technology.Methodology & results: Optimization of the original ELISA and assay redevelopment using different antibody pairs did not result in substantive improvements, necessitating implementation of an alternative technology for assay development.Conclusion: We highlight the challenges encountered with optimization/redevelopment of the original ELISA and discuss results of the new assay on the Gyros platform.